(untitled) (Recoletos Multidisciplinary Research Journal, 2019)
Depressive symptomatology is among the major psychological problems experienced by adolescents. Sex differences in the occurrence of depressive symptoms have likewise been extensively reported in literature. However, a great majority of related research have primarily been carried out in the Western context. Hence, we conducted a study to identify the prevalence of depressive symptoms among Malaysian adolescents, and to determine its relationship with certain risk factors as well as the potential moderating role of sex. The sample comprised 964 adolescents from 20 secondary schools across Malaysia. Using logistic regression, results demonstrated that stressful life events and maternal verbal aggression significantly predicted symptoms of depression. In the moderation tests, sex significantly interacted with stressful life events and parental verbal aggression in predicting depressive symptoms. Hence, there is evidence to suggest that the depressogenic impact of stressful life events and parental verbal aggression on depressive symptomatology differs between male and female adolescents.